Advanced research methods and their applications on the nexus of energy efficiency and environment: evidence from five RCEP economies. Issue 1 (31st December 2022) - Zhang, Feng; Huang, Yongming; Nan, Xiaoli
Abstract: Using efficient and cleaner energy is environmentally friendly and is vital for combating the negative effect of emissions on the environment. Focusing on both developed and developing nations, it is important to report their environmental conditions while targeting economic and energy-related factors. In this regard, the current study is an attempt to investigate the influence of energy efficiency (ENEF), financial inclusion (FIN), economic growth (GDP), environmental-related technological innovation (ERTI), and human capital index (HCI) on the carbon dioxide (CO2 ) emissions for the five selected nations of RCEP. The variables are found associated in terms of long-run cointegration relationships. The panel quantile regression estimator is utilized for empirical estimations, which provide highly significant estimates across the three selected quantiles (25th, 50th and 75th). The results report that FIN and GDP significantly aggravate environmental degradation by enhancing the CO2 emission level, among which the strongest CO2 emission growth is found in the second quantile. Besides, the ENEF, ERTI and HCI significantly reduce CO2 emission. Based on the empirical findings, this study provides practical implication focusing on the improvement of energy efficiency policies and revising financial inclusion policies in promotion of green investments.